Pure Conducting Polymer Hydrogels Increase Signal‐to‐Noise of Cutaneous Electrodes by Lowering Skin Interface Impedance - Roubert Martinez, Sebastian; Le Floch, Paul; Liu, Jia; Howe, Robert D. (Advanced healthcare materials, 2023)
Cutaneous electrodes are routinely used for noninvasive electrophysiological sensing of signals from the brain, the heart, and the neuromuscular system. These bioelectronic signals propagate as ionic charge from their sources to the skin–electrode interface where they are then sensed as electronic charge by the instrumentation. However, these signals suffer from low signal‐to‐noise ratio arising from the high impedance at the tissue‐to‐electrode contact interface. This paper reports that soft conductive polymer hydrogels made purely of poly(3,4‐ethylenedioxy‐thiophene) doped with poly(styrene sulfonate) present nearly an order of magnitude decrease in the skin–electrode contact impedance (88%, 82%, and 77% at 10, 100, and 1 kHz, respectively) when compared to clinical electrodes in an ex vivo model that isolates the bioelectrochemical features of a single skin–electrode contact. Integrating these pure soft conductive polymer blocks into an adhesive wearable sensor enables high fidelity bioelectronic signals with higher signal‐to‐noise ratio (average 2.1 dB increase, max 3.4 dB increase) when compared to clinical electrodes across all subjects. The utility of these electrodes is demonstrated in a neural interface application. The conductive polymer hydrogels enable electromyogram‐based velocity control of a robotic arm to complete a pick and place task. This work provides a basis for the characterization and use of conductive polymer hydrogels to better couple human and machine. Pure conducting polymer hydrogels are found to exhibit increased signal‐to‐noise ratio on humans compared to clinical cutaneous electrodes. Isolating the bioelectrochemical relationship between skin and the conducting polymer hydrogels using a novel ex vivo model, this paper concludes that this signal‐to‐noise relationship arises from dramatically reduced skin–interface impedance. The increased signal‐to‐noise ratio is leveraged in a sensitive real‐time robotic neural interface.